Humanity in Conflict: Examining the Roots of Israeli-Palestinian Conflict - Makarim, Tabriz (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The Israeli-Palestinian conflict is an episodic humanitarian crisis that demands a permanent resolution. The obligation to end the Promised Land atrocity should not depend on the two states involved. The international community's responsibility to conclude the contention is part of the responsibility to defend humanity. Based on that reason, the research is conducted to find the basis of the conflict with a four-stage analysis based on heuristic analysis, critical study, interpretation, and historiography. Those four are a culmination process of collecting information needed before reconstructing to understand the nature of the conflict and find common ground to solve the issue. From this study’s findings, the conflict that occurred in Israel-Palestine is based on an illogical basis, especially considering national interests. Therefore, there is an urgency to draw the conflict based on political realism and constructive dialogues to return to the first purpose of peacefully co-existing.